2018
DOI: 10.4236/tel.2018.815220
|View full text |Cite
|
Sign up to set email alerts
|

Panel Data Analysis of Profitability Determinants: Evidence from Indian Telecom Companies

Abstract: The elements determining the profitability of companies have warranted special attention over time. The levels of rising debt, increased concerns for liquidity and risks of bankruptcy have impacted the revenue of manufacturing sector companies in general and service sector companies in particular. In this study, an attempt has been made to study the financial health of companies belonging to Indian telecom industry. For this purpose, a balanced panel dataset of five Indian telecom companies listed on National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 22 publications
(16 reference statements)
7
27
1
1
Order By: Relevance
“…There was also no causal affiliation between lnGRO and lnROE. This finding was in tandem with Khan et al (2018) whose research on five listed telecommunication companies in India found no significant connection between growth and the firms' financial performance. The finding also supported Meseret and Getahun (2017) and Vuong (2017) whose studies uncovered no material association between growth and firms' viability.…”
Section: Granger Causality Test Resultssupporting
confidence: 55%
“…There was also no causal affiliation between lnGRO and lnROE. This finding was in tandem with Khan et al (2018) whose research on five listed telecommunication companies in India found no significant connection between growth and the firms' financial performance. The finding also supported Meseret and Getahun (2017) and Vuong (2017) whose studies uncovered no material association between growth and firms' viability.…”
Section: Granger Causality Test Resultssupporting
confidence: 55%
“…The firm size helps the firm to increase its profitability by expanding its capacity more efficiently. The findings of the study show positive impact on profitability supporting Prasetyantoko and Rachmadi (2008), Khan et al (2018), Ehi-Oshio et al 2013, Zaid et al (2014), and Al-Jafari and Samman (2015) but varying from Goddard, Tavakoli, and Wilson (2005) and Aparna (2015). The higher expense to revenue ratio of the firm indicates lower profitability.…”
Section: 919supporting
confidence: 49%
“…Khan et al (2018),Aparna (2015),Prempeh et al (2018) but varying from Ehi-Oshio et al(2013),Maroa and Kioko (2016), andEgbunike and Okerekeoti (2018).Business firm learns how to minimize costs and maximize profits with time. Thus, the age of the firm creates an active impact on profitability.…”
mentioning
confidence: 99%
“…Many researchers used ROA and ROE as measures of profitability, including Rezina, Ashraf, and Khan (2020); Prasetyantoko and Rachmadi (2008); Khan, Shamim, and Goyal (2018); Pratheepan (2014); Zaid, Wan Muhd, and Zulqernain (2014); Ehi-Oshio, Adeyemi, and Enofe (2013); Nanda and Panda (2018); Chen and Tseng (2005); Aissa and Lefa (2016); Liuspita and Purwanto (2019); Ifeduni and Charles (2018) and Yazdanfar (2013).…”
Section: Literature Reviewmentioning
confidence: 99%